Managing Political Risk - shams -o sadat zahedi (مطالعات مدیریت بهبود و تحول, 1994)
There are many Iranian companies that are working abroad and many international organizations that are operating within our national boarder. One of the important factors that influences their activities is political risk. International companies are working in a complex political environment which is not easy to assess and manage. The political environments provide opportunities and drawbacks, and determine the strategies that international organizations develop. This article focuses on the concept of political risk, assessing and managing its various types. Generally, the more positive political environment, the more integrative approaches a company apt to employ. In negative environment, however, defensive approaches are preferred.